Gestores educacionais para a educação inclusiva: arranjos e tramas na contemporaneidade - Noya, Carolina Pereira (2016)
In this research, I have attempted to problematize the spread of discourses in which the alliance between educational management and school inclusion is a powerful production strategy in the contemporary school. In order to do that, I have addressed the following issue: how has the education of Inclusive Education managers been produced in contemporary educational discourses? In this exercise of thought, I have used the Foucauldian notions of discourse, power/knowledge relations and governmentality as conceptual and methodological tools. Hence, the analysis has been inspired by Foucauldian Studies in Education following the post-structuralist thought. Noticing the importance of thinking about the relations established in arrangements and intertwinings between management and inclusion, I searched for documents and programs intended to inclusion manager education on the website of the Secretary of Continuing Education, Literacy, Diversity and Inclusion (SECADI). By analyzing the discursive recurrences in the official documents and investigating how managers actions in Inclusive Education have been produced, I noticed the appeal to new ways of being a manager that are also involved in the comprehension of both the Special Education as a knowledge area and the difference in the processes of manager education for inclusion. Such discursivity is set in the need for involving everyone in inclusion management by means of the principles of democratic management. The displacement from the emphasis on the management discourses to the educational management has been regarded in this research as a current strategy of conduct of teachers. The present emphasis on the discourse of management decentralization towards the Inclusive Education has intensified the centrality on the manager, who is required to produce ways of being in the contemporary school, under the democratic, participation and leadership discourses.